Opportunistic Monetary Policy: an Alternative Rationalization - Patrick Minford; Naveen Srinivasan (Cardiff University, Cardiff Business School, 2005)
This paper offers an alternative rationalization for opportunistic behaviour i.e., a gradual disinflation strategy where policymakers react asymmetrically to supply shocks, opting to disinflate only in recessionary period. Specifically, we show that adaptive expectations combined with asymmetry in the Phillips curve of a specific sort together provide an optimizing justification for opportunism. However, the empirical basis for these conditions to be satisfied in the current low-inflation context of most OECD countries remains however to be established.
Keywords: E52; E58; 330; Deliberate disinflation; Opportunistic disinflation